Experiments and non-linear MHD simulations of hot vertical displacement events in ASDEX-Upgrade. (1st May 2023) - Schwarz, N; Artola, F J; Hoelzl, M; Bernert, M; Brida, D; Giannone, L; Maraschek, M; Papp, G; Pautasso, G; Sieglin, B; Zammuto, I; Upgrade Team, the ASDEX; et al.
Abstract: Hot vertical displacement events (VDEs) are one of the worst case scenarios for high-current tokamaks as they are associated with large heat loads and electro-magnetic forces. Non-linear magneto-hydrodynamic (MHD) simulations of the thermal and current quench can help to understand their dynamics and consequences. In order to make predictions for future devices, the validation of codes against present machines is crucial. Dedicated experiments were performed in ASDEX Upgrade to provide a basis for simulations with the non-linear extended MHD code JOREK. 2D as well as non-axisymmetric simulations at realistic parameters can reproduce quantities like the edge safety factor q 95 at the thermal quench onset, the halo current magnitude and the level of vertical forces, while the exact width of the halo current area requires more sophisticated boundary conditions and is left for future work. Small horizontal forces are observed during the hot VDEs in the experiment as well as in the simulations.